THE PROBLEM OF 3 YEARS OLD CHILDREN IN PRONOUNCING CONSONANT ( A CASE OF DAMAR'S PHONOLOGICAL ACQUISITION) - ASRIANI HASIBUAN S.Pd., M.Hum (Jurnal Education and Development, 2016)
The objective of this research entitled The Problems of 3 Years Old Children in Pronouncing Consonant was todescribe the phonological process of an infant and to describe the reason why he produces [ r ] sound becomes [ l ] sound.This research applied the descriptive qualitative method. The subject of this research is a child in three years old, namelyDamar.In collecting data, Damar is asked to pronounce some words which contain “r” in it. After he pronounced thewords, the researcher recorded it and transcripted it. The results of this research showed that A child is not born being ableto produce all the sounds and sound patterns of his/her language. As a child is learning how to speak English, he willsimplify sounds and sound patterns. For this research, Damar has disorder in producing the sound. And the sounds deviateto the other sounds which are produced in the same area, that is “r” and “l.”